Implementasi kurikulum Merdeka melalui Profil Pelajar Pancasila dalam menguatkan karakter siswa SMPN 178 JAKARTA - Okta Rosfiani; Nisrina Maisun; Fatimah Azzahra; Ariansyah Ariansyah (Journal of Innovative and Creativity, 2025)
Despite its importance in developing students' character within the current educational environment, there is a scarcity of research on how the Merdeka Curriculum is applied in conjunction with the Profile of Pancasila Students in junior high schools.high schools, which is what inspired this study. In order to improve character education, the study intends to investigate how teachers and students internalize and put into practice the values found in the Pancasila Student Profile.A qualitative descriptive method was employed, involving teachers and students from chosen public junior high schools, selected through intentional sampling. Data were collected using observation, documentation, and in-depth interviews, and analyzed using thematic analysis. The discoveries uncover that the execution of the Merdeka Educational programs through the six measurements of Students' discipline, empathy, and responsibility are positively impacted by the Pancasila Understudy Profile's confidence and dedication, global diversity, shared involvement, autonomy, basic consideration, and inventiveness. Nonetheless, there are still issues with instructors' comprehension and support networks. The study comes to the conclusion that a comprehensive and consistent strategy is necessary for character education using this curriculum.Theoretically, this research contributes to the understanding of curriculum implementation From the viewpoint of character development, it offers suggestions for schools to enhance internal cooperation and improve teacher training. Further studies are suggested to investigate the lasting effects of this method in various educational settings